Kualitas Pelayanan Terhadap Kepuasan Pelanggan Menggunakan Metode Customer Satisfaction Index dan Importance Performance Analysis Pada PT. PLN (Persero) Area Meulaboh - Sofiyanurriyanti Sofiyanurriyanti; Yola Tri Amanda; Arie Saputra; Marlinda Marlinda; Iing Pamungkas; Indra Kusuma (Jurnal Optimalisasi, 2021)
The level of customer satisfaction with service is an important factor in developing a service provision system that is responsive to customer needs. Based on the results of this study, namely the results of the CSI calculation, the customer satisfaction index value for the services provided by the PLN Meulaboh Area is 86% on a scale range of 85% < X 89% so that it can be said that the level of customer satisfaction there is generally in the Very Good category. means very good but there is still a sense of dissatisfaction from customers of PT. PLN (Persero) Meulaboh Area is 14%, therefore the service level of PT. PLN (Persero) Meulaboh Area should be further improved. Based on the results of the calculation of the level of conformity with the interests of the customer, it can be seen clearly from the Cartesian diagram, where there are 6 attributes that need to be repaired immediately, namely (P6) the accuracy of each record made by the meter reader officer, (P10) The condition of the KWH meter (turnover of numbers). according to the amount of usage), (P11) the speed of response in serving requests for submitting new pairs or changes in power, (P13) the lack of speed in the procedures for installing new connections or simple power changes, (P16) smooth processing of electricity payments through local banks and (P16) P24) compensation to customers for mistakes made by officers.